Debating public administration : management challenges, choices, and opportunities - Durant, Robert F., 1949-; Durant, Jennifer R. S. (Boca Raton, Fl. : CRC Press, 2013)
'Informed by a'5 R' framework (reconceptualizing purpose, redefining rationality, recapitalizing human assets, reengaging resources, and revitalizing democratic constitutionalism), this book bridges the gap between theory and practice. In this collection of articles revised for book format, the Durants expertly draw out themes, issues, problems, and prospects in their preface and section introductions. Bulleted lessons and practical take-aways are also added for the busy practitioner and researcher. This book is a'one stop shop' for cross-disciplinary, cross-sectoral, and cross-professional exchanges on contemporary challenges, choices, and opportunities facing public administrators today'--
'Preface Theory to Practice Advancing the'science, processes, and art of public administration' has long been a central animating purpose of the American Society for Public Administration (ASPA). Such a mission today involves practitioners and scholars providing answers to what is arguably the central animating question facing societies worldwide: how, when, and with what implications for the values treasured in a democratic republic can we best harness for public purposes the dynamism of markets, the passion and commitment of nonprofit and nongovernmental organizations, and the public interest-oriented expertise of the career public service at all levels of government. But dialogue between practitioners and academics has increasingly become the exception rather than the rule in contemporary public administration circles. With this set of challenges in mind, the then-new PAR editor Richard Stillman and managing editor Jos Raadschelders generously asked me to develop a feature for the journal that would be tailored to the information needs of practitioners while simultaneously affording scholars state-of-the-art summaries of the status of current research. As such, my interrelated aims as editor of Theory to Practice (T2P) were fourfold: ?? Afford opportunities for academics, practitioners, and pracademics to inform each other's work in the hope of advancing both practice and theory building in public administration ?? Facilitate cross-disciplinary, cross-sectoral (public, private, and nonprofit), and cross-professional exchanges that break down contemporary tendencies toward fragmentation and'stovepiping' of knowledge applicable to both practice and theory ??'--
Includes bibliographical references and index.
Keywords: Public administration